ESTIMATION OF STATURE FROM FINGER MEASUREMENTS AMONG THE POPULATION OF KARNATAKA STATE - Lakshmi K, Shri; Deepthi, Hari; Taur G, Vikrantsing; Sridhar, Tavishi; P, Hrideek; Kallumpurat, Akhilesh; Thomas, Mebin Wilson; Simon, Monica (Journal of Forensic Medicine and Toxicology, 2025)
Forensic investigations often face challenges in identifying corpses when traditional methods are infeasible due to severe body damage. Hence, estimating stature through anthropometric parameters becomes valuable for identification. For forensic applications, this study aims to establish a correlation between finger length and stature in the Karnataka population. Finger lengths from 200 participants (115 females and 85 males) aged 18-30 from Karnataka were measured using vernier calipers, and stature was recorded with anthropometric rods. Participants with finger disabilities were excluded. Each finger was measured three times for precision, and statistical analyses were conducted using SPSS software. Pearson correlation coefficients and multiple regression analyses were used to evaluate the relationship between finger length and stature, with a significance level set at p
Keywords: Forensic Anthropology; Anthropometry; Stature Estimation; Finger Length